Sustainable Fashion - Kasem,Nuur (2019)
Background: The fashion industry is one of the world’s largest and most creative sectors in the retail industry, but also one of the most polluting industries globally. More and more clothes are produced than it is needed, and this has been a usual process in the fashion industry to meet consumers’ needs. Consumers can also be responsible for the environmental degradation, even though most of the environmental impact is attributed to the fashion industry because consumers can be mindless actors with no control over the environmental impact of fashion products. Due to these several issues the fashion industry has been moving towards more sustainable trends by introducing new materials for fashion products to be more sustainable, intending to transform the fashion industry for the greater good, by rethinking how to produce and perceive textiles. The goal with the new materials is to use available resources to substitute the scarce resources. Aim: This study aims to understand what consumers associate with the term sustainability in consumption of ready-made clothing, how important sustainability is for them when shopping and consuming ready-made clothing and what they consider as sustainable fashion, regarding ready-made clothing that consists of conventional materials as well as new materials. Theories: Today sustainable consumption demands rational decisions; which consumers should meet despite conflicting sources of information. Consumers are becoming increasingly interested in the environmental consequences associated with their consumption patterns and they are using different strategies to shop and consume sustainably. However, different complexities may arise for consumers who are trying to be sustainable when shopping and consuming fashion products. Methodology: A mixed-method of induction and deduction was applied in this research. Henceforth, the research method is based on abduction. This research also applied subjective epistemology and constructionist ontology, because the aim was to understand consumers in the context of sustainability and new materials in fashion products. First, qualitative methods such as a pilot interview and netnography were conducted to get knowledge about the empirical field. Second, the empirical data was gathered by conducting two focus group interviews and a questionnaire with 64 participants. The empirical data was then analyzed with the theories. Conclusions: There are increasing interest and awareness among consumers for sustainability and new materials in ready-made clothes in the fashion industry. Consumers also desire to get more knowledge from companies and that companies become more transparent with them. Consumers also mention that other aspects of sustainability, such as the consumption, production, manufacturing and working conditions in the industry, and not only the materials in clothes are also important to take into consideration, that changing the materials in clothes is not enough for becoming more sustainable.
Keywords: Fashion; new materials; consumption; sustainability